2008
DOI: 10.1093/hmg/ddn131
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dissection of ALS-associated toxicity of SOD1 in transgenic mice using an exon-fusion approach

Abstract: Mutations in Cu,Zn superoxide dismutase (SOD1) are associated with amyotrophic lateral sclerosis (ALS). Among more than 100 ALS-associated SOD1 mutations, premature termination codon (PTC) mutations exclusively occur in exon 5, the last exon of SOD1. The molecular basis of ALS-associated toxicity of the mutant SOD1 is not fully understood. Here, we show that nonsense-mediated mRNA decay (NMD) underlies clearance of mutant mRNA with a PTC in the non-terminal exons. To further define the crucial ALS-associated S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…In our previous studies of SOD1 inclusions in spinal cord of SOD1-linked FALS patients and SOD1 transgenic mice, we observed that antigen retrieval methodology played an essential role in detection of SOD1 inclusions in lower motor neurons 21, 22 , especially in some human cases (unpublished data). We compared three antigen retrieval protocols: boiling and microwave that are most commonly used, and high pressure decloaking chamber.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…In our previous studies of SOD1 inclusions in spinal cord of SOD1-linked FALS patients and SOD1 transgenic mice, we observed that antigen retrieval methodology played an essential role in detection of SOD1 inclusions in lower motor neurons 21, 22 , especially in some human cases (unpublished data). We compared three antigen retrieval protocols: boiling and microwave that are most commonly used, and high pressure decloaking chamber.…”
Section: Resultsmentioning
confidence: 87%
“…2 and supplementary figure 1), but not in the four FALS cases with SOD1 mutations. Previous studies have demonstrated that SOD1/ubiqutin-positive inclusions in spinal motor neurons are a pathological hallmark in ALS patients with SOD1 mutations and in the transgenic mice overexpressing mutant SOD1 18, 22 . Supporting the notion that the FUS-positive inclusions are absent in SOD1-linked ALS, we found that the ubiquitin-positive inclusions in spinal neurons were FUS-negative in patients with SOD1 G85R or SOD1 A4V mutation and in the transgenic mice overexpressing SOD1 G93A and SOD1 L126Z 21, 23 (Supplementary figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that nonsense-mediated mRNA decay underlies the clearance of SOD1 mRNA with a premature termination codon in exons 1-4, but not in exon 5. 16 This is why among the reported SOD1 ALS mutations, stop codon mutations exclusively occur in exon 5. It is possible that nonsense-mediated decay could be involved in the degradation of the alternatively spliced SOD1 mRNA, which could be more efficient in spinal cord tissue than in blood cells, since the level of SOD1 transcript without exon 2 was lower in the spinal cord (figure 3).…”
mentioning
confidence: 99%
“…Some transition metals such as iron, cobalt, zinc, selenium, molybdenum, magnesium, chromium, manganese and copper are essential for life. Others, such as mercury, lead, nickel, cadmium, palladium, and arsenic are widely used in industry and in various implants but are toxic at certain levels in humans [7][8][9].…”
Section: Heavy Metals Intoxicationmentioning
confidence: 99%